1995
DOI: 10.1210/jcem.80.2.7852527
|View full text |Cite
|
Sign up to set email alerts
|

The impact of estrogen on adrenal androgen sensitivity and secretion in polycystic ovary syndrome.

Abstract: Adrenal hyperandrogenism is a common feature of patients with polycystic ovary syndrome (PCO). This may be due to enhanced adrenal sensitivity to ACTH. Because enhanced ovarian androgen secretion does not appear to explain this phenomenon, we explored the role of estrogen in inducing enhanced adrenal sensitivity, in that a state of relative hyperestrogenism exists in PCO. Eight patients with PCO and seven matched controls received ovine corticotropin-releasing hormone (oCRH; 0.1 micrograms/kg) iv before and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
3
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 20 publications
5
42
3
1
Order By: Relevance
“…In the current study, normo-and hyperandrogenic PCOS patients demonstrated equal ratios of progesterones (17-OHP4/17-OHPE p = 0.837), suggesting equal 3β-HSDII activity in these groups for the conversion of 17-OHPE to 17-OHP4. Equivalent 3β-HSDII activity was previously reported for the comparison between healthy women and PCOS patients (13). Using DHEAS as a surrogate for DHEA, the higher A/DHEAS ratio in hyperandrogenic patients found in the current study suggests higher 3β-HSDII activity specifically for the conversion of DHEA to A.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…In the current study, normo-and hyperandrogenic PCOS patients demonstrated equal ratios of progesterones (17-OHP4/17-OHPE p = 0.837), suggesting equal 3β-HSDII activity in these groups for the conversion of 17-OHPE to 17-OHP4. Equivalent 3β-HSDII activity was previously reported for the comparison between healthy women and PCOS patients (13). Using DHEAS as a surrogate for DHEA, the higher A/DHEAS ratio in hyperandrogenic patients found in the current study suggests higher 3β-HSDII activity specifically for the conversion of DHEA to A.…”
Section: Discussionsupporting
confidence: 72%
“…The increase in 17,20 lyase activity was also seen in PCOS patients, even after diagnostic standardization, and it was attributed to the phosphorylation of Ser/Thr residues, cytochrome b5, and cytochrome c allosteric actions (22)(23)(24). In fact, P450c17α dysregulation has been attributed to the modulatory effects of cytochrome b5, insulin, and estradiol (13,23). In the current study, estradiol levels were not increased in the hyperandrogenic group, and this finding does not support previous observations indicating that estrogen may increase 17,20 lyase activity in the conversion of 17-OHP4 to A in PCOS patients (13,14).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations